Evaluation of GFAP/UCH-L1 biomarkers for computed tomography exclusion in mild traumatic brain injury (mTBI) - Jacopo M. Legramante; Marilena Minieri; Marzia Belli; Alfredo Giovannelli; Alessia Agnoli; Daniela Bajo; Lorenza Bellincampi; Anna Maria De Angelis; Alessandro Terrinoni; Massimo Pieri; Eleonora Nicolai; Vito N. Di Lecce; et al. (International Journal of Emergency Medicine)
Abstract Introduction Mild traumatic brain injury (mTBI) represents a major public health concern and affects millions of people worldwide every year. Diagnosis mainly relies on clinical criteria and computed tomography (CT) scans. GFAP (glial fibrillary acidic protein) and UCH-L1 (ubiquitin carboxyl-terminal hydrolase-L1) have been recently studied as potential biomarkers of mTBI. This study retrospectively evaluated the possible use of these combined biomarkers as negative predictors for excluding brain injuries in patients with suspected mTBI in the emergency department. Methods Adult patients (n = 130) enrolled at Tor Vergata University Hospital (Rome, Italy), consecutively registered at the triage of the emergency department between October 2022 and January 2023, with non-penetrating TBI and Glasgow Coma Scale (GCS) score of 13–15, were considered. All eligible patients underwent intracranial CT scans and blood tests, within 12 h after trauma, for GFAP and UCH-L1 serum concentrations. Results Intracranial CT detected injuries in only seven patients (5%); GFAP and UCH-L1 tested positive in 96 patients and negative in 34 patients (74% vs. 26%). Combined biomarkers had a sensitivity equal to 1.00 (95% CI 0.64-1.00) and a negative predictive value (NPV) of 1.00 (0.99-1.00) in mTBI diagnosis with a negative CT. Conclusions Combined laboratory tests for GFAP and UCH-L1 biomarkers might play a potential clinical role in avoiding unnecessary head CT scans after mTBI in emergency departments.